Modelling the optimization of world-class 400 m and 1,500 m running performances using high-resolution data - Le Hyaric, Antoine; Aftalion, Amandine; Hanley, Brian (Frontiers in Sports and Active Living, 2024)
The 400m and 1500m are track events that rely on different but important contributions from both the aerobic and anaerobic energy systems. The purpose of this study is to model men's and women's 400m and 1500m championship performances to gain a deeper understanding of the key mechanical and physiological factors affecting running speed and bend running using high-resolution data from live competition (10 Hz). To investigate World-class athletes' instantaneous speeds, propulsive forces and aerobic and anaerobic energy, we model and simulate the performances of the men's and women's European Athletics 400m champions, Matthew Hudson-Smith and Femke Bol, as well as the men's European Athletics 1500m champion, Jakob Ingebrigtsen, and the women's European Athletics U23 1500m champion, Gaia Sabbatini. The simulations show that a fast start is essential in both the 400m and 1500m because of the need for fast oxygen kinetics, with peak running speeds occurring within the first ~50 m in both events. Subsequently, 400m athletes slow continually from this maximum speed to the finish, and a total anaerobic contribution of ~77% is found for both male and female champions.The key to faster 400m racing is to reduce the decrease in velocity: this comes from both a high VO2 and a high anaerobic contribution. Ingebrigtsen's winning tactic in the European 1500m final is to adopt a very fast cruising pace from 300 m onwards that is possible because he is able to maintain a high VO2 value until the end of the race and has a large anaerobic contribution. He has fast VO2 kinetics that does not require as fast a start as his opponents, but then he speeds up in the last two laps, without a fast sprint finish. The comparison between Sabbatini's slower and quicker races (~8 s difference) shows that it is the improvement of aerobic metabolism that has the greatest effect on 1500m performance. Coaches should note in particular that the all-out pacing nature of the 400m requires the prioritization of anaerobic energy system development, and those who coach the 1500m should note the differing energy contributions between even-paced races and championship racing.